How Feasible is Adequate Yearly Progress (AYP)? Simulations of School AYP "Uniform Averaging" and "Safe Harbor" under the No Child Left Behind Act - Jaekyung Lee (Arizona State University, 2004)
The No Child Left Behind Act of 2001 (NCLB) requires that schools make "adequate yearly progress" (AYP) towards the goal of having 100 percent of their students become proficient by year 2013-14. Through simulation analyses of Maine and Kentucky school performance data collected during the 1990s, this study investigates how feasible schools would have met the AYP targets if the mandate had been applied in the past with "uniform averaging (rolling averages)" and "safe harbor" options that have potential to help reduce the number of schools needing improvement or corrective action. Contrary to some expectations, the applications of both options would do little to reduce the risk of massive school failure due to unreasonably high AYP targets for all student groups. Implications of the results for the NCLB school accountability system and possible ways to make the current AYP more feasible and fair are discussed.